Youth Roles In Developing Village Economies - I Nengah Suarmanayasa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the role of youth as dynamic, motivating, and innovative forces in rural development planning, as well as to identify the obstacles they face. The study employs a descriptive method with a qualitative approach, using three data collection techniques: observation, interviews, and documentation. Data analysis involves data reduction, presentation, and conclusion drawing. However, there are several obstacles that hinder the youth's ability to carry out village area development, including the government's lack of concern for the development of Pegagan Julu youth and the high ego nature of the youth. The research findings indicate that youth in villages play a crucial role as dynamists, motivators, and innovators in rural development planning. However, there are several obstacles that hinder the youth's ability to carry out village area development, including the government's lack of concern for the development of Pegagan Julu youth and the high ego nature of the youth. However, there are several obstacles that hinder the youth's ability to carry out village area development, including the government's lack of concern for the development of Pegagan Julu youth and the high ego nature of the youth. It is important to address these obstacles to ensure successful rural development planning.